The Role Of Organizational Commitment Mediation On The Effect Of Servant Leadership On Performance - Quoc, Anh Nguyen; Ghauri, Pervez N (Yayasan Pendidikan Belajar Berdikari, 2022)
Study This goal For the purpose of understanding how organizational ones' commitment to mediation affects performance. Utilize a quantitative, descriptive, and verifiable approach. Using a survey and random sampling, data are collected. Respondents are private sector lecturers at 29 universities in Central Java. Using the Process Macro AF Hayes SPSS plug-in, analyze mediation. The findings of the analysis demonstrate that servant leadership has a good influence on performance, as well as organizational commitment, and that these three factors work together to positively affect Servant Leadership. This indicates that performance levels will increase when organizational commitment is high. This conclusion can be understood to mean that the lecturer has a higher level of ownership in the organization, which in turn has a higher level of positive servant leadership influence on the lecturer's performance.